Pembuatan dan Pendampingan Sistem Informasi Portal Desa Tadukan Raga - Egi Afandi; Trinanda Syahputra; Ahmad Fitry Boy; Dedi Setiawan; Amrullah Amrullah; Firahmi Rizky; Marnoko Marnoko (CERED Indonesia Publishing, 2023)
The village is a very important part in determining the success of development and is in direct contact with the community, especially in public services. Digitization can be interpreted as a process of storing all the properties and information of text, sound, images or multimedia in an electronic string of zeros and ones. The village is the most accurate data source for searching population data. The Village Information System makes it easier for Villages to compile digital data and information about the objective conditions of the Village, to prepare Village Development plans based on detailed and real data. Tadukan Raga is a village in the Sinembah sub-district of Tanjung Muda Hilir, Deli Serdang Regency, North Sumatra province, Indonesia. There are 5 hamlets, namely: Hamlet I Tungkusan, Hamlet II, Hamlet III Sei Basah, Hamlet IV Lottery, Hamlet V Kampung Dalam. From the results of the development of the Tadukan Raga Village Portal Information System which has been completed, it can be concluded that the Village portal system can assist the Village in disseminating Village activities and policies, so that appeals made by the Village can be easily accepted by the community and can be well documented every activity carried out by the village.